1998
DOI: 10.1183/09031936.98.11051128
|View full text |Cite
|
Sign up to set email alerts
|

Forced oscillation technique for the evaluation of severe sleep apnoea/hypopnoea syndrome: a pilot study

Abstract: Patients with obstructive sleep apnoea/hypopnoea syndrome (SAHS) experience repeated episodes of increased upper airway resistance leading to profound disturbances in sleep architecture and arterial blood gases [1,2]. Repeated inspiratory efforts occur during an obstructive sleep apnoea until arousal ensues and airway patency is restored [3]. The increased upper airway resistance in patients with SAHS can be assessed indirectly by the analysis of different signals, such as the time profile of the inspiratory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 18 publications
(21 reference statements)
4
40
0
Order By: Relevance
“…Frequency analysis of the EEG signal was carried out and no evidence of neurological activation was found. These findings are consistent with the clinical experience with FOT [3][4][5]. Significant effects on the upper airway or the EEG produced by the use of FOT, with and without CPAP, were not observed in subjects with SAHS.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Frequency analysis of the EEG signal was carried out and no evidence of neurological activation was found. These findings are consistent with the clinical experience with FOT [3][4][5]. Significant effects on the upper airway or the EEG produced by the use of FOT, with and without CPAP, were not observed in subjects with SAHS.…”
Section: Discussionsupporting
confidence: 80%
“…13 The forced oscillation technique (FOT) is a simple and noninvasive method that allows continuous online monitoring of airflow obstruction during sleep, even in the absence of flow, as occurs in apnoeas. FOT has been applied in clinical diagnostic studies in patients with sleep apnoea/hypopnoea syndrome (SAHS) [1][2][3][4] and in continuous positive airway pressure (CPAP) titration studies [5,6] with highly encouraging results.…”
mentioning
confidence: 99%
“…Multi-frequency is preferred in studies exploring the patterns or mechanisms of the frequency dependence of Zrs in health and disease. In contrast, single-frequency is used in the study of relatively rapid changes in Zrs, such as the changes observed during the respiratory cycle (Dellacà et al, 2004), deglutition apnea (Souza et al, 2008), deep inspiration (Slats et al 2007), and the evaluation of airway patency in sleep apnea (Badia et al, 1998;Lemes et al, 2003). A characteristic feature of COPD is that Zrs is often very different between inspiration and expiration, in contrast to the situation in normal subjects (Dellaca et al, 2007;Bates et al, 2011).…”
Section: Mono-frequencymentioning
confidence: 99%
“…Previous studies in patients with OSA have indicated that major upper airway narrowing or collapse can be reliably identified when the impedance value increases to levels more than twice baseline values during tidal breathing [16,27]. Therefore, for the various categories of respiratory events we determined the proportion of events for which |Z| exceeded this value.…”
Section: Measurements Of Impedance Values |Z| During Apnoeas and Hypomentioning
confidence: 99%